Can rescuers accurately deliver subtle changes to chest compression depth if recommended by future guidelines?. (March 2018) - Deakin, Charles D.; Sidebottom, David B.; Potter, Ryan
Abstract: Background: A recent study reported that a compression depth of 4.56 cm optimised survival following cardiac arrest, which is at variance with the current guidelines of 5.0–6.0 cm. A reduction in recommended compression depth is only likely to improve survival if healthcare professionals can accurately deliver a relatively small change in target depth. This study aimed to determine if healthcare professionals could accurately judge their delivered compression depth by 0.5 cm increments. Method: This randomised interventional trial asked BLS-trained healthcare professionals to complete two minutes of continuous chest compressions on an adult manikin, randomised (without any feedback device), to compress to one of three target depth ranges of 4.0–5.0 cm, 4.5–5.5 cm or 5.0–6.0 cm, at the recommended rate of 100–120 compressions min −1 . Basic demographic data, compression rate, and compression depth were recorded. Results: One hundred and one participants were recruited, of whom one withdrew. Median depths of 3.66 cm (IQR: 3.37–4.16 cm), 4.13 cm (IQR: 3.65–4.36 cm) and 4.76 cm (IQR: 4.16–5.24 cm) were found for the target depths of 4.0–5.0 cm (n = 30), 4.5–5.5 cm (n = 35) and 5.0–6.0 cm (n = 35) respectively (P < 0.001). Overall, 18 participants successfully compressed to their target depth. Conclusions: Rescuers are able to judge 0.5 cm differences in compression depth with precision, but remain unable to accurately judge overall target depth. Reducing the current recommended compression depth to 4.56 cm is likely to result in delivered compressions significantly below the optimal depth.